Solar cells : materials, manufacture and operation - McEvoy, A. J. (Academic Press, 2013)
Enormous leaps forward in the efficiency and the economy of solar cells are being made at a furious pace. New materials and manufacturing processes have opened up new realms of possibility for the application of solar cells. Crystalline silicon cells are increasingly making way for thin film cells, which are spawning experimentation with third-generation high-efficiency multijunction cells, carbon-nanotube based cells, UV light for voltage enhancement, and the use of the infrared spectrum for night-time operation, to name only a few recent advances. This thoroughly updated new edition of Markvart and Castaner's Solar Cells, extracted from their industry standard Practical Handbook of Photovoltaics, is the definitive reference covering the science and operation, materials and manufacture of solar cells. It is essential reading for engineers, installers, designers, and policy-makers who need to understand the science behind the solar cells of today, and tomorrow, in order to take solar energy to the next level. A thorough update to the definitive reference to solar cells, created by a cast of international experts from industry and academia to ensure the highest quality information from multiple perspectivesCovers the whole spectrum of solar cell information, from basic scientific background, to the latest advances in materials, to manufacturing issues, to testing and calibration. Case studies, practical examples and reports on the latest advances take the new edition of this amazing resource beyond a simple amalgamation of a vast amount of knowledge, into the realm of real world applications.